PCSK9 inhibitors in a renal transplant patient complicated with hepatitis B: A case report and literature review - Lv, Pinchao; Li, Yuxi; Wu, Lin; Weng, Haoyu; Chen, Ming; Ding, Wenhui; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Disorders of lipid metabolism is recognized to be one of the most frequent complications of renal transplantation, dyslipidemia and CKD are strong risk factors for ASCVD (arteriosclerotic cardiovascular disease). As the novel lipid‐lowering drug PCSK9i (proprotein convertase subtilisin/ kexin type 9 inhibitors) , the safety and efficacy of which in transplanted patients are yet to be confirmed. There have been several small-sample studies using PCSK9i in patients after heart transplantation, while fewer cases using PCSK9i after kidney transplantation. We report a case of a renal transplant recipient complicated with Hepatitis B treated with PCSK9i, which achieved a remarkable lipid lowering efficacy, and no significant adverse effects were found during the follow-up.